National Health Interview Survey, 1992: AIDS Knowledge and Attitudes Supplement ([Verlag nicht ermittelbar], 1994)
The purpose of the National Health Interview Survey (NHIS) is to obtain information about the amount and distribution of illness, its effects in terms of disability and chronic impairments, and the kinds of health services people receive. This supplement includes variables from the NHIS core Person File (see NATIONAL HEALTH INTERVIEW SURVEY, 1992 [ICPSR 6343]), including sex, age, race, marital status, veteran status, education, income, industry and occupation codes, and limits on activity. Variables unique to this supplement cover attitudes toward and knowledge of Acquired Immune Deficiency Syndrome (AIDS), the effects of the disease, how it is spread, where to obtain information on AIDS, blood tests, how to avoid getting the disease, and personal knowledge of anyone who had had the test for AIDS, had tested positively for the virus, or had the disease. In addition, questions were asked concerning awareness of the drug AZT, perceptions of the effectiveness of condoms, and knowledge of condom use.